Rating Stock Price with the Price Earning Ratio (PER): a Case Study on the Shares of Food and Beverage Industry in the Indo - Nazwirman, Nazwirman (UI Scholars Hub, 2008)
Stock exchange investment gives return more than saving money in bank. For instance, in form of a deposit with average of 6 % per annum. But investor must be analyze carefully in buying shares. Using one analytical share techniques, the price earning ratio (PER) method. Investor will easily know which share they should buy. Price earning ratio method in analyzing the share of food and beverage company in Indonesian stock exchange use three alternative (k*= 11%, k*=16% and k*=21%). From 15 company on listing, only 6 companies give dividend to investor every year. Company share to buy only one share company, because for three alternative PER < PER* so the return from the share to more than 11%, 6% or 21% and price from the share is cheap. There are share 5 companies that are not good to buy, but good to sell to investor, because three alternative PER>PER* meaning advantage from share smaller than 11%, 6% or 21%.